Defect-rich UiO-66@g-C3N4/Ni frameworks as efficient water splitting photocatalysts - Jamma A.; Jaksani B.; Vennapoosa C.S.; Gonuguntla S.; Sk S.; Ahmadipour M.; Abraham B M.; Mondal I.; Pal U. (Royal Society of Chemistry, 2025)
In this report, we uncover the synergistic role of g-C3N4, a cocatalyst (Ni), and defect sites of Zr-MOFs for unprecedented hydrogen evolution activity. Further, the interaction between defect rich UiO-66-D and g-C3N4 is well-supported by theoretical understanding and photocatalysis trends. The key role in the enhanced activity is further substantiated by considering the abundant type-II heterojunction between UiO-66-D and g-C3N4 in the hybrid composite. This study emphasizes the significance of defect-induced local strain and modification of the electronic structure at the junction connecting UiO-66 and g-C3N4 along with Ni NPs, demonstrating their role in the catalytic activity. Ligand oriented defect engineering is deliberately utilized to manipulate photonic and electrical attributes of the UiO-66 framework. Improved catalytic performance is ascribed to structural stabilization of the composite by the introduction of unsaturation in UiO-66 and suitable coordinated Ni NPs over g-C3N4, resulting in a multi-fold enhancement of the hydrogen production rate of 2.6 mmol g?1 h?1 with an AQY of 6.41% at 420 nm as compared to the pristine material. ? 2024 RSC.